A Bivalent Inhibitor of Prostate Specific Membrane Antigen Radiolabeled with Copper‐64 with High Tumor Uptake and Retention. (5th September 2019) - Zia, Nicholas A.; Cullinane, Carleen; Van Zuylekom, Jessica K.; Waldeck, Kelly; McInnes, Lachlan E.; Buncic, Gojko; Haskali, Mohammad B.; Roselt, Peter D.; Hicks, Rodney J.; Donnelly, Paul S.
Abstract: Molecules containing lysine‐ureido‐glutamate functional groups bind to the active site of prostate specific membrane antigen, which is overexpressed in prostate cancer. To prepare copper radiopharmaceuticals for the diagnosis and therapy of prostate cancer, macrobicyclic sarcophagine ligands tethered to either one or two lysine‐ureido‐glutamate functional groups through an appropriate linker have been prepared. Sarcophagine ligands can be readily radiolabeled with positron‐emitting copper‐64 at room temperature. The bivalent agent, in which two targeting groups are tethered to a single copper complex, dramatically outperforms the monomeric agent with respect to tumor uptake and retention. The high tumor uptake, low background, and prolonged tumor retention, even at 24 hours post injection, suggest the bivalent agent is a promising diagnostic for prostate cancer and could be used for prospective dosimetry for therapy with a copper‐67 variant. Abstract : Ein potentielles Kontrastmittel und Therapeutikum zur Behandlung von Prostatakrebs, mit guter Aufnahme und Speicherung durch den Tumor, ist durch die Verkettung zweier Lysin‐Ureido‐Glutamat‐Peptide hergestellt worden. Der Wirkstoff bindet an einen Prostata‐spezifisches Antigen, an einen einzelnen Sarcophagin‐Kupfer‐Komplex.